2020
DOI: 10.3389/fimmu.2020.01516
|View full text |Cite
|
Sign up to set email alerts
|

IgG Subclass Determines Suppression Versus Enhancement of Humoral Alloimmunity to Kell RBC Antigens in Mice

Abstract: It has long been appreciated that immunoglobulins are not just the effector endpoint of humoral immunity, but rather have a complex role in regulating antibody responses themselves. Donor derived anti-RhD IgG has been used for over 50 years as an immunoprophylactic to prevent maternal alloimmunization to RhD. Although anti-RhD has dramatically decreased rates of hemolytic disease of the fetus and newborn (for the RhD alloantigen), anti-RhD also fails in some cases, and can even paradoxically enhance immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Including this report, this has now repeatedly been observed with 5 different RBC donor strains (HOD, K1, KEL Hi , KEL Med , and KEL Lo ) and three different monoclonal antibodies (anti-K1, anti-Kp b , and anti-HOD). The mechanisms by which IgG2c enhances alloimmunization is unclear; however we have reported that in the case of HOD and K1, Fc gamma receptors on dendritic cells are required (16,17). Moreover, for the HOD system, IgG2c resulted in an increase in proliferation of HOD specific CD4+ T cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Including this report, this has now repeatedly been observed with 5 different RBC donor strains (HOD, K1, KEL Hi , KEL Med , and KEL Lo ) and three different monoclonal antibodies (anti-K1, anti-Kp b , and anti-HOD). The mechanisms by which IgG2c enhances alloimmunization is unclear; however we have reported that in the case of HOD and K1, Fc gamma receptors on dendritic cells are required (16,17). Moreover, for the HOD system, IgG2c resulted in an increase in proliferation of HOD specific CD4+ T cells.…”
Section: Discussionmentioning
confidence: 93%
“…KEL RBCs). Indirect antiglobulin tests, which also measure antigen-modulation, were carried out by staining with PUMA3 followed by goat-anti-mouse Ig APC and using the same gating strategy (16,17).…”
Section: Determining Post-transfusion Circulation Antibody Binding Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible explanation for this observation is that the strain of mice used for the study may not be expressing IgG2a. Shinde et al (2020) reported that in some strains of mice there is no expression of IgG2a; instead these mice express the novel IgG2c. Thus, it can be inferred that IgG2a is not a useful immunoglobulin subclass to monitor immune responses to recombinant hepatitis B surface antigen vaccine in non-IgG2a expressing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for this observation is that the strain of mice used for the study may not be expressing IgG2a. Shinde et al [38] reported that in some strains of mice there is no expression of IgG2a; instead these mice express the novel IgG2c. Thus, it can be inferred that IgG2a is not a useful immunoglobulin subclass to monitor immune responses to recombinant hepatitis B surface antigen vaccine in non-IgG2a expressing mice.…”
Section: Plos Onementioning
confidence: 99%